Living in the Ottoman realm bempire and identity, 13th to 20th centuries - Isom-Verhaaren, Christine; Schull, Kent F. (Indiana University Press, 2016)
"Living in the Ottoman Realm brings the Ottoman Empire to life in all of its ethnic, religious, linguistic, and geographic diversity. The contributors explore the development and transformation of identity over the long span of the empire's existence